Experimental assessment and multi-objective optimization on the engine characteristics of reactivity controlled compression ignition engine powered by Ternary fuel. (15th November 2022) - Ashok, Athmakuri; Gugulothu, Santhosh Kumar; Venkat Reddy, Ragireddy; Deepanraj, Balakrishnan; Rajendran, Saravanan; Arthi, Manivannan
Graphical abstract: Highlights: Multi objective optimisation is adopted to operate the operating parameters with ternary fuel on RCCI engine. ANOVA, a statistically valid test is used to develop a regression model. Biodiesel enriched engine resulted in 2.55% higher NHRR and 6.48% higher CP. HC and NOx emissions decreased by 5.86% and 11.4%, at higher FIP. Ternary fuel performs effectively at higher FIP. Abstract: In light of global energy insecurity and other pressing concerns like global warming, stringent emissions, and rapid industrialization, researchers are looking at the potential for alternative fuel research as a fossil fuel substitute. The present research work is carried out to study the influence of injection strategies (i.e., FIP and FIT) by varying the engine load at a constant velocity of 2000 rpm. The effect of several parameters such as engine load, FIT, and FIP on an RCCI engine fuelled with B20/1-pentanol fuel is examined using an L20 orthogonal array for an RCCI engine fuelled with B20/1-pentanol fuel. Various models were constructed and validated with the aid of experimental results. The ideal engine parameters found were 62.06% of engine load, FIP of 438.5 bar, and 27 0bTDC, and under this configuration, the output obtained is as follows: 206.9 ppm, 25.09 ppm, 33.04 J/deg, 29.39% and 2.39 kW for NOx, HC, HRR, BTE and BP emission respectively. Also, the regression model is developed using ANOVA, a statistically reliable test, and the test results suggest that the regression model is acceptable for the following. The following are the R 2 values obtained: NOx − 99.78%, HC– 99.14%, NHRR- 98.5%, BTE-99.93%, and BP-99.96% respectively.